AN ERROR ANALYSIS IN WRITING DESCRIPTIVE TEXT OF THE EIGHTH GRADE STUDENT OF JUNIOR HIGH SCHOOL IN CIANJUR - Ika Rustiani; Efransyah Efransyah (IKIP Siliwangi, 2022)
Writing is one of the skills in English. The five components of writing that must be grasped are content, organization, vocabulary, mechanics, and grammar. English grammar is different from Indonesian grammar. Therefore, many students still have difficulty in writing texts by paying attention to aspects of writing. Especially in the grammatical aspect, there are still many errors made by students. The goals of this research is to find out kinds of errors in writing descriptive texts of the eighth grade students of junior high school in cianjur. The descriptive qualitative method was employed in this research. The research instrument was acquired from the students' tests. The result showed that the errors made by students based on Dulay (1982) was four type of the grammarical errors, they were omission (14 with percentage 18%), addition (27 with percentage 35%), misformation (33 with percentage 42%), dan misordering (4 with percentage 5%). It means that misformation was the most common grammar error type committed by students. Keywords: Writing, Error Analysis, Descriptive Text